(untitled) (Revista de Estudos da Linguagem, 2004)
The main purpose of this paper is to make evident that many lexical items of the portuguese language cannot be seen as exceptions to the pretonic mid vowels raising rules as they have been considered, and that lexical diffusion is not lexical analogy.